2014
DOI: 10.1080/19404476.2014.11462114
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Responsive Teacher Practices in Supporting Academic Motivation at the Middle Level

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 40 publications
(106 reference statements)
2
12
0
Order By: Relevance
“…High teacher expectations tend to correlate with high student achievement (Figlio & Lucas, 2000), but this association is complex, involving diverse and/or subjective bidirectional influences between teachers and students. Aside from student achievement, teacher expectations also contribute to adolescent psychosocial well-being and student academic motivation (Ikeda, Crawford, & Woodward-Lopez, 2006; Kiefer et al, 2014).…”
Section: Teacher Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…High teacher expectations tend to correlate with high student achievement (Figlio & Lucas, 2000), but this association is complex, involving diverse and/or subjective bidirectional influences between teachers and students. Aside from student achievement, teacher expectations also contribute to adolescent psychosocial well-being and student academic motivation (Ikeda, Crawford, & Woodward-Lopez, 2006; Kiefer et al, 2014).…”
Section: Teacher Expectationsmentioning
confidence: 99%
“…It is in the middle school environment that behaviors may emerge such as chronic absenteeism, failed courses, and school suspensions that can serve as robust indicators of subsequent high school dropout (Balfanz, MacIver, & Herzog, 2007). Given these challenges, middle school has been identified as an environment that may not adequately meet students’ needs and has been found uniquely difficult for educators, evidenced by high turnover rates among middle school teachers (Byrnes & Ruby, 2007; Clotfelter, Ladd, & Vigdor, 2007; Kiefer, Ellerbrock, & Alley, 2014; Marinell & Coca, 2013).…”
mentioning
confidence: 99%
“…Empson (2014) examined second grade students' learning of base 10 concepts through a responsive teaching approach. Kiefer, Ellerbrock, & Alley (2014) examined the effects of responsive teaching strategies on middle school students in a variety of content areas. Responsive teaching has also been associated widely with teaching and learning mathematics and science concepts across the grade spectrum (e.g.…”
Section: Responding To Studentsmentioning
confidence: 99%
“…This finding is consistent with past research showing that students (especially those making transitions during early adolescence) benefit from knowing there is an adult in school who cares about their personal wellbeing and who is committed to their academic success ( Newman, Lohman, Newman, Myers, & Smith, 2000 ). Additionally, Keifer, Ellerbrock, and Alley (2014) underscored the value of building relationships that are perceived by middle level students as high in care, as students who feel adults in school care for them are more likely to report a range of positive student outcomes. Finally, Gorard and See (2011) suggested that supportive student-teacher relationships may be a potential source of enjoyment available to middle level students.…”
Section: Discussionmentioning
confidence: 99%